Potential of siam weed extract in combination with Trichoderma harzianum to stimulate seed germination of Coffea arabica - Ania Ningsih, Misbahul; Pancaningtyas, Sulistyani; Su'udi, Mukhamad (Pelita Perkebunan (a Coffee and Cocoa Research Journal), 2024)
The Arabica coffee (Coffea arabica) beans feature a solid and thick seed shape that obstructs the germination process. Seed germination is an important feature of coffee plant cultivation and significantly impacts on the growth and development of the coffee plant. Siam weed (Chromolaena odorata L.) has the potential to be used as an organic fertilizer due to its nutrients and secondary metabolite compounds which can help accelerate plant growth. The optimal use of organic fertilizer can be achieved by using Trichoderma harzianum. This research aims to determine the effect and optimal concentration of Siam weed extract (Chromolaena odorata L.) and Trichoderma harzianum on the germination of Arabica coffee seeds. The research used a factorial Completely Randomized Design (CRD) in the form of siam weed extract concentrations of 8 ppm and 16 ppm and concentrations of Trichoderma harzianum of 5 ppm, 10 ppm, 15 ppm, and 20 ppm. The research finding indicated that the C2T1 treatment had the best results in terms of germination, growth speed, growth synchrony, hypocotyl length, and number of leaves on coffee plants. Meanwhile, the C2T4 treatment had the highest chlorophyll content.